The Influence of Liaison Officer and Business Consultant on MSMEs Dismsum Mentai and Dapur Sheeqa Development through the Preparation, Implementation, and Accomplishment Stages in the Polbeng Business Expo Chapter II - Rahmah Yusrini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Micro, Small, and Medium Enterprises (MSMEs) require structured assistance to strengthen marketing, digital adoption, operational readiness, and financial management. This study examines the contribution of Liaison Officers (LOs) and Business Consultants (BCs) to the development of Dimsum Mentai and Dapur Sheeqa through the Preparation, Implementation, and Accomplishment stages of Polbeng Business Expo Chapter II. A qualitative project-based case study approach was employed using direct observation, project documentation, promotional materials, financial reports, and field notes. During the preparation stage, the assistance focused on identifying business needs and developing business profiles, profile and promotional videos, product catalogs, digital marketing plans, QRIS facilities, and financial reporting formats. During implementation, the LOs coordinated communication and operational activities, while the BCs supported product presentation, customer service, digital promotion, business operations, and transaction recording. The accomplishment stage evaluated the outputs and financial performance of both MSMEs. The results show that the assistance improved promotional readiness, digital visibility, cashless payment capability, and financial administration. Dimsum Mentai recorded May 2025 revenue of IDR 26,969,000 and net profit of IDR 14,327,000, while Dapur Sheeqa recorded revenue of IDR 21,307,000 and net profit of IDR 11,805,000. The findings indicate that project-based collaboration between higher education institutions and MSMEs can integrate mentoring, digital transformation, and financial evaluation to support professional business management, competitiveness, and sustainable MSME development.